Evaluation of fetal arrhythmias by echocardiography. - Allan, L D (1983)
The normal fetal heart shows variation in rate and rhythm. Twenty three cases that fell outside the normal patterns of variation of heart rate and rhythm were evaluated by echocardiography. Ten showed atrial or ventricular extrasystoles and these were not associated with perinatal morbidity or mortality. Seven cases showed complete heart block, two in association with structural cardiac abnormality. Six cases were of supraventricular tachycardia, five of which were successfully treated and one was delivered prematurely. It was possible to diagnose accurately the type of arrhythmia using the M-mode echocardiogram to compare the relation between atrial and ventricular contraction. Cross-sectional echocardiography allowed identification of associated structural abnormalities. Recognition that an arrhythmia is present and appropriate prenatal treatment if this is indicated will avoid unnecessary operative or premature deliveries.